Anti-cancer activity of 7-methoxyheptaphylline from Clausena harmandiana against PANC-1 pancreatic cancer cells and its sustainable extraction method - Juthamart Maneenet; Suresh Awale; Chantana Boonyarat; Pornthip Waiwut; Rawiwun Kaewamatawong (PLoS ONE, 2025)
Pancreatic cancer presents a significant therapeutic challenge characterized by poor survival rates, leading to development of innovative treatment strategies. This study evaluated the anti-cancer potential of 7-methoxyheptaphylline (7-MH), a carbazole alkaloid from Clausena harmandiana, against pancreatic cancer cells (PANC-1) and developed an environmentally sustainable extraction methodology using ultrasonic-assisted extraction (UAE). 7-MH demonstrated selective cytotoxicity against PANC-1 cells with preferential activity under nutrient deprivation conditions (PC50 = 4.54 μM) compared to nutrient-rich conditions (IC50 = 46.84 μM). This compound exhibited minimal toxicity toward normal MCE301 epithelial cells (IC50 = 83.4 μM). Live-cell imaging showed dose-dependent apoptotic morphology including membrane blebbing and cell shrinkage within 24 hours. At concentrations of 25 and 50 μM, the compound significantly inhibited wound closure and colony formation, suggesting antimetastatic properties. Mechanistic analysis exhibited that 7-MH suppressed the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling pathway specially under nutrient deprived conditions. Western blot analysis showed 45% reduction in Akt expression, 43% decrease in mTOR phosphorylation, and complete inhibition of Akt phosphorylation at 20 µM concentration. For sustainable extraction of 7-MH, UAE using ethanol was optimized through response surface methodology (RSM) with central composite design (CCD). The optimal protocol (50 °C, 60 minutes, 0.40 g/10 mL plant/solvent ratio) achieved 1.26 ± 0.02% yield with only 3.55% deviation from predicted values. This developed extraction method provides an efficient and environmentally sustainable alternative to conventional halogenated solvent extraction methods. These findings offer valuable insights for advancing natural product-based cancer therapeutics and demonstrate the implementation of sustainable natural products extraction principles.